Design of Mucoadhesive Strips for Buccal Fast Release of Tramadol - Nayla Francine Garcia Pastório; Camila Felix Vecchi; Rafaela Said dos Santos; Marcos Luciano Bruschi (MDPI AG, 2021)
Tramadol hydrochloride is a synthetic analogue of codeine and shows activity on the central nervous system as an opioid agonist and inhibitor of serotonin and norepinephrine reuptake. It has been used for controlling moderate to severe pain. Mucoadhesive fast-dissolving films can present greater drug availability and patient acceptance when compared to the systems of peroral administration. The films were prepared using the solvent casting method with ethylcellulose, polyvinylpyrrolidone and poly(vinyl alcohol). The effect of each polymer concentration was investigated using a 2³ factorial design with repetition at the central point. The formulations were subjected to physicochemical, mechanical, ex vivo mucoadhesive and in vitro drug release profile analysis. These properties were dependent on the polymeric composition (independent factors) of each system. The optimized formulations showed good macroscopic characteristics, improved resistance to bending, rigidity, rapid swelling up to 60 s, improved mechanical and mucoadhesive characteristics, and also fast dissolving and tramadol release. The optimized formulations constitute platforms and strategies to improve the therapy of tramadol with regard to availability at the site of application, considering the necessity of rapid pain relief, and show potential for in vivo evaluation.